2010
DOI: 10.1149/1.3391447
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Investigation of the Initial Oxidation of the FeCrAlRE Alloy Kanthal AF in Dry and Wet O[sub 2] at 600 and 800°C

Abstract: The FeCrAlRE (where RE is reactive element) alloy Kanthal AF was exposed isothermally at 600 and 800°C for 72 h in dry normalO2 and in normalO2 with 10 vol % normalH2O . The mass gains were 3–5 times higher at the higher temperature. The presence of water vapor increased the oxidation rate at 800°C , while no significant effect was observed at 600°C . A thin two-layered oxide formed at 600°C : an outer (Fe,Cr)2normalO3 corundum-type oxide, containing some Al, and an inner, probably amorphous, Al-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
5
12
0
Order By: Relevance
“…The chromia band corresponds to Cr 2 O 3 which was identified using XRD while the alumina in the film was apparently non-crystalline. This is in accordance with a recent study of Canovic et al [20] who reports that the oxide film formed on Kanthal Ò AF in O 2 and O 2 ? H 2 O at 600°C consists of a top corundum-type layer and a bottom layer made up of non-crystalline alumina.…”
Section: Discussionsupporting
confidence: 94%
“…The chromia band corresponds to Cr 2 O 3 which was identified using XRD while the alumina in the film was apparently non-crystalline. This is in accordance with a recent study of Canovic et al [20] who reports that the oxide film formed on Kanthal Ò AF in O 2 and O 2 ? H 2 O at 600°C consists of a top corundum-type layer and a bottom layer made up of non-crystalline alumina.…”
Section: Discussionsupporting
confidence: 94%
“…6,15), no crystalline aluminas can be detected with XRD. This is also in accordance with Josefsson et al [15] and Canovic et al [22], who reported that FeCrAl oxidation produces no crystalline aluminas at 500 and 600°C. However, Josefsson et al [15] detected a-Al 2 O 3 after 168 h at 700°C.…”
supporting
confidence: 92%
“…10b). [15,16,22]. It is notable that, although the oxide film is dominated by aluminium oxide (see Figs.…”
mentioning
confidence: 96%
“…15 In the present study, attempts to identify the alumina formed on the two alloys by nano-diffraction methods indicated that it was not crystalline. Formation of protective alumina layers -the role of Cr.-It is wellknown that the oxidation properties of alumina-forming alloys are improved by chromium.…”
Section: Reaction Of Kcl On the Surface-mentioning
confidence: 53%